Differing predictive relationships between baseline LDL-C, systolic blood pressure, and cardiovascular outcomes. (1st November 2016) - Deedwania, Prakash C.; Pedersen, Terje R.; DeMicco, David A.; Breazna, Andrei; Betteridge, D. John; Hitman, Graham A.; Durrington, Paul; Neil, Andrew; ,
Abstract: Background: Traditional cardiovascular risk factors, such as hypertension and dyslipidemia, predispose individuals to cardiovascular disease, particularly patients with diabetes. We investigated the predictive value of baseline systolic blood pressure (SBP) and low-density lipoprotein cholesterol (LDL-C) on the risk of vascular outcomes in a large population of patients at high risk of future cardiovascular events. Methods: Data were pooled from the TNT (Treating to New Targets), CARDS (Collaborative Atorvastatin Diabetes Study), and IDEAL (Incremental Decrease in End-Points Through Aggressive Lipid Lowering) trials and included a total of 21, 727 patients (TNT: 10, 001; CARDS: 2838; IDEAL: 8888). The effect of baseline SBP and LDL-C on cardiovascular events, coronary events, and stroke was evaluated using a multivariate Cox proportional-hazards model. Results: Overall, risk of cardiovascular events was significantly higher for patients with higher baseline SBP or LDL-C. Higher baseline SBP was significantly predictive of stroke but not coronary events. Conversely, higher baseline LDL-C was significantly predictive of coronary events but not stroke. Results from the subgroup with diabetes (5408 patients; TNT: 1501; CARDS: 2838; IDEAL: 1069) were broadly consistent with those of the total cohort: baseline SBP and LDL-C were significantly predictive of cardiovascular events overall, with the association to LDL-C predominantly related to an effect on coronary events. However, baseline SBP was not predictive of either coronary or stroke events in the pooled diabetic population. Conclusions: In this cohort of high-risk patients, baseline SBP and LDL-C were significantly predictive of cardiovascular outcomes, but this effect may differ between the cerebrovascular and coronary systems. Trial Registration Number :NCT00327691 (TNT);NCT00327418 (CARDS);NCT00159835 (IDEAL). Highlights: Incremental increases in SBP/LDL-C predicted future CV events in high-risk patients. These effects appeared to differ between the coronary and cerebrovascular systems. Determining various contributions of risk factors to CV risk could improve CVD care.